Esforço para inovação tecnológica : uma caracterização da indústria de alimentos do município de Marília/SP. - Abreu, Andréia de (Universidade Federal de São Carlos, 2007)
In the light of the entrepreneurial scenario, in which new competitiveness patterns were established, companies have been forced to search for new manners of action in order to survive the market. Among these forms, it is highlighted those which favor the development of technological innovations and the establishment of cooperation relationships among several partners. This same reality applies to the foodstuff industry. The development of technological innovations has been increasingly important since they are capable of providing the products the market need, as well as aimed at guaranteeing food safety throughout its production and as final good already ready to consumption. Another manner the companies adopt to overcome troubles and become more innovative is the insertion in cooperative ventures, which occurs because these companies do not have necessary resources, including knowledge to adopt and transfer innovation to their products and processes, or because they want to reduce the risks related to innovation practices. According to this scenario, the present work in intended for characterizing the efforts to establish technological innovation and cooperative relationships to innovation on foodstuff companies based in Marília, São Paulo, thus making possible to identify actions to aid the development and adoption of technologies in the companies studied. Besides, this work is aimed at identifying and evaluating how these cooperation relationships are established. In order to do so, case studies were carried out in four foodstuff companies. As a result, it was verified that the companies promoted a great deal of effort in order to introduce technological innovation to their products, processes or both.
Keywords: Inovações tecnológicas; Alimentos - indústria; Cooperação para inovação; Aprendizagem organizacional; Estratégia tecnológica; Technological Innovation; Cooperation to Innovate; Foodstuff Industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO